Analysis of the Cochrane Review: Electronic Cigarettes for Smoking Cessation and Reduction. Cochrane Database Syst Rev. 2014,12: CD010216. - Vaz-Carneiro, António (2015)
Smoking is one of the most important risk factors for various cardiovascular, cancer and respiratory diseases. There are a number of smoking cessation techniques involving psychological, pharmacological and behavioral interventions, with varying effectiveness and different costs. The electronic cigarettes are devices which produce a nicotine aerosol but without the toxic products of tobacco smoke, and they have become popular as a potential intervention for smoking cessation. The present review analyzed the evidence published of this approach for the treatment of tobacco dependence and concluded that there is reasonable evidence of its clinical effectiveness. We present and discuss the findings of this systematic review, with practical contextualization.